Interplay between finance and institutions in the development process of the industrial sector: Evidence from South Africa - Adewale Samuel Hassan; Daniel Meyer (Journal of Risk and Financial Management, 2022)
Despite the importance of the financial system and quality of institutions to the attainment of economic development goals, the mediating role of institutions in how finance influences the development of the industrial sector across countries has not been given adequate attention in the literature. Therefore, this study assessed the moderating role of institutions in the relationship between finance and industrial development of South Africa for the period 1984-2021. To evaluate the long-run relationship among the variables, the combined cointegration test of Bayer and Hanck was used, while fully modified least squares, dynamic least squares and canonical cointegrating regression were employed to estimate elasticity relationships. The findings of the study revealed that finance impacts industrial development positively in South Africa, but this positive impact is diminished by the quality of institutions in the country. Therefore, the financial system in South Africa needs to be rooted in a high-quality institutional structure for its beneficial impact on the industrial sector to be reinforced for sustainable development. Moreover, there is a need for more reforms in the financial system to promote efficiency that would translate growth in finance into more inclusive growth gains in the industrial sector.
Keywords: 650; finance; institutions; industrial sector; development; cointegration; South Africa